2002
DOI: 10.5597/lajam00017
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the franciscana (<i>Pontoporia blainvillei</i>) off southeastern Brazil: sexual dimorphism, growth and geographic variation

Abstract: Variations in body and skull morphology may exhibit geographic differences evidencing distinct population stocks. The objectives of the present study were to analyze such variation to test the hypothesis of a disjunct distribution of the franciscana (Pontoporia blainvillei) off the southeastern coast of Brazil. Body length and 39 cranial variables were measured from bycaught animals to considered sexual, ontogenetic and geographic variations. The areas studied were Espírito Santo (ES) (18º30S-19º40S), northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 21 publications
4
38
1
Order By: Relevance
“…This suggested a model based upon a single sample of both sexes, with its increased precision due to larger sample size, may be preferable. Several morphometric and genetic studies (Pinedo, 1991(Pinedo, , 1995Secchi et al, 1998Secchi et al, , 2003aOtt et al, 2002;Ramos et al, 2002;Lázaro et al, 2004;Barreto and Rosas, 2006) have established the existence of three franciscana morphotypes/genotypes: one found in FMA I (Rio de Janeiro and Espírito Santo states, Brazil); a second one in FMA II (from São Paulo to Santa Catarina states, Brazil) and the third in FMA III and IV (from Rio Grande do Sul state, Brazil down to Buenos Aires Province, Argentina). Animals inhabiting FMA I are smaller than animals from FMA III and IV but larger than those from FMA II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested a model based upon a single sample of both sexes, with its increased precision due to larger sample size, may be preferable. Several morphometric and genetic studies (Pinedo, 1991(Pinedo, , 1995Secchi et al, 1998Secchi et al, , 2003aOtt et al, 2002;Ramos et al, 2002;Lázaro et al, 2004;Barreto and Rosas, 2006) have established the existence of three franciscana morphotypes/genotypes: one found in FMA I (Rio de Janeiro and Espírito Santo states, Brazil); a second one in FMA II (from São Paulo to Santa Catarina states, Brazil) and the third in FMA III and IV (from Rio Grande do Sul state, Brazil down to Buenos Aires Province, Argentina). Animals inhabiting FMA I are smaller than animals from FMA III and IV but larger than those from FMA II.…”
Section: Discussionmentioning
confidence: 99%
“…Franciscanas inhabiting the southern end of this range are larger than the individuals from the northern end. Conversely, individuals from the central area of distribution are the smallest of all (Pinedo, 1991(Pinedo, , 1995Ramos et al, 2002;Barreto and Rosas, 2006). Body size affects all aspects of an organism's physiology and morphology, thereby influencing life history traits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the variation within P. blainvillei has been attributed to a north-south disjunction in geographic distribution resulting in 2 subpopulations (Pinedo 1991;Ramos et al 2002;Secchi et al 1998). However, this distributional hiatus, often mentioned for Santa Catarina State (Brazil), cannot be supported because regular records of the species (Cherem et al 2004) and a resident population have been recently reported (Cremer and Simões-Lopes 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately other approaches including morphological and molecular analyses have been used successfully for determining stock units (e.g. Pinedo, 1991;Secchi et al, 1998;Higa et al, 2002;Ramos et al, 2002;Secchi et al, 2003;Lázaro et al, 2004).…”
Section: Final Considerationsmentioning
confidence: 99%
“…Previous research based on morphological (Pinedo, 1991;Higa et al, 2002;Ramos et al, 2002) and genetic data (Secchi et al, 1998;Lázaro et al, 2004) have suggested the existence of at least two clearly defined stocks of franciscana, one to the north of Santa Catarina (~29°S), Brazil and the other to the south. Furthermore, a phylogeographic analysis by Secchi et al (2003) (combining mtDNA data, morphometrics, and lifehistory parameters) provided evidence for separating the species into four management stocks: two inhabiting coastal waters of Brazil, the third occurring in Rio Grande do Sul state (southern Brazil) and Uruguay, and the fourth in coastal Argentinean waters.…”
Section: Introductionmentioning
confidence: 99%